Repair and mutagenesis of plasmid DNA modified by ultraviolet irradiation or N-acetoxy-N-2-acetylaminofluorene. - Schmid, S E (1982)
Plasmid DNA was modified in vitro to various extents with N-acetoxy-N-2-acetylaminofluorene or UV irradiation. The modified plasmid DNAs were then used to transform Escherichia coli strains having different repair capabilities. Both survival and mutagenesis frequencies of the plasmid were measured as a function of the number of lesions per plasmid molecule. The majority of N-2-acetylaminofluorene (AAF) adducts, like thymine dimers, were repaired by the excision (uvrA+-dependent) pathway. In rec+ strains, dose-dependent mutagenesis occurred in either AAF- or UV-modified plasmid DNA. This is in contrast with results obtained in recA- strains, in which only AAF adducts gave rise to a lower, but dose-dependent, mutagenesis frequency. In these recA- strains there was no UV mutagenesis. Unlike what is observed with phages, induction of the "SOS" functions by UV irradiation of the bacteria prior to transformation did not increase the survival or the mutagenesis of the plasmid.